A Chemical Biology Toolbox Targeting the Intracellular Binding Site of CCR9: Fluorescent Ligands, New Drug Leads and PROTACs - Huber, Max; Toy, Lara; Schmidt, Maximilian; Vogt, Hannah; Budzinski, Julian; Wiefhoff, Martin F. J.; Merten, Nicole; Kostenis, Evi; Weikert, Dorothée; Schiedel, Matthias (Angewandte Chemie International Edition, 2022)
A conserved intracellular allosteric binding site (IABS) has recently been identified at several G protein-coupled receptors (GPCRs). Starting from vercirnon, an intracellular C-C chemokine receptor type 9 (CCR9) antagonist and previous phase III clinical candidate for the treatment of Crohn's disease, we developed a chemical biology toolbox targeting the IABS of CCR9. We first synthesized a fluorescent ligand enabling equilibrium and kinetic binding studies via NanoBRET as well as fluorescence microscopy. Applying this molecular tool in a membrane-based setup and in living cells, we discovered a 4-aminopyrimidine analogue as a new intracellular CCR9 antagonist with improved affinity. To chemically induce CCR9 degradation, we then developed the first PROTAC targeting the IABS of GPCRs. In a proof-of-principle study, we succeeded in showing that our CCR9-PROTAC is able to reduce CCR9 levels, thereby offering an unprecedented approach to modulate GPCR activity.
CRIS-Team WoS Importer:2022-02-11

Bivalent ligands promote endosomal trafficking of the dopamine D3 receptor-neurotensin receptor 1 heterodimer - Budzinski, Julian; Maschauer, Simone; Kobayashi, Hiroyuki; Couvineau, Pierre; Vogt, Hannah; Gmeiner, Peter; Roggenhofer, Anna; Prante, Olaf; Bouvier, Michel; Weikert, Dorothée (Communications Biology, 2021)
Bivalent ligands are composed of two pharmacophores connected by a spacer of variable size. These ligands are able to simultaneously recognize two binding sites, for example in a G protein-coupled receptor heterodimer, resulting in enhanced binding affinity. Taking advantage of previously described heterobivalent dopamine-neurotensin receptor ligands, we demonstrate specific interactions between dopamine D3 (D3R) and neurotensin receptor 1 (NTSR1), two receptors with expression in overlapping brain areas that are associated with neuropsychiatric diseases and addiction. Bivalent ligand binding to D3R-NTSR1 dimers results in picomolar binding affinity and high selectivity compared to the binding to monomeric receptors. Specificity of the ligands for the D3R-NTSR1 receptor pair over D2R-NTSR1 dimers can be achieved by a careful choice of the linker length. Bivalent ligands enhance and stabilize the receptor-receptor interaction leading to NTSR1-controlled internalization of D3R into endosomes via recruitment of β-arrestin, highlighting a potential mechanism for dimer-specific receptor trafficking and signalling.
CRIS-Team Scopus Importer:2021-09-24

Development of a Fluorescent Ligand for the Intracellular Allosteric Binding Site of the Neurotensin Receptor 1 - Vogt, Hannah; Shinkwin, Patrick; Huber, Max; Staffen, Nico; Hübner, Harald; Gmeiner, Peter; Schiedel, Matthias; Weikert, Dorothée (ACS Pharmacology & Translational Science, 2024)
The membrane protein family of G protein-coupled receptors (GPCRs) represents a major class of drug targets. Over the last years, the presence of additional intracellular binding sites besides the canonical orthosteric binding pocket has been demonstrated for an increasing number of GPCRs. Allosteric modulators harnessing these pockets may represent valuable alternatives when targeting the orthosteric pocket is not successful for drug development. Starting from SBI-553, a recently discovered intracellular allosteric modulator for neurotensin receptor subtype 1 (NTSR1), we developed the fluorescent molecular probe 14. Compound 14 binds to NTSR1 with an affinity of 0.68 μM in the presence of the agonist NT(8-13). NanoBRET-based ligand binding assays with 14 were established to derive the affinity and structure-activity relationships for allosteric NTSR1 modulators in a direct and nonisotopic manner, thereby facilitating the search for and optimization of novel allosteric NTSR1 ligands. As a consequence of cooperativity between the ligands binding to the allosteric and orthosteric pocket, compound 14 can also be used to investigate orthosteric NTSR1 agonists and antagonists. Moreover, employing 14 as a probe in a drug library screening, we identified novel chemotypes as binders for the intracellular allosteric SBI-553 binding pocket of NTSR1 with single-digit micromolar affinity. These hits may serve as interesting starting points for the development of novel intracellular allosteric ligands for NTSR1 as a highly interesting yet unexploited drug target in the fields of pain and addiction disorder therapy.
CRIS-Team Scopus Importer:2024-05-03
Keywords: allosteric modulator; BRET; functional selectivity; GPCR; in vitro assay; screening